2015
DOI: 10.1016/j.econlet.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the effects of negative framing in linear public goods games

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 13 publications
(13 reference statements)
7
33
0
Order By: Relevance
“…Andreoni (1999) [1] found that in a linear public goods game, subjects were much more cooperative under a positive frame than a negative frame. Park (2000) [2] and Sonnemans et al (1998) [3] found similar results, which were later decomposed into different components in Cox (2015) [4]. Thus, we must use the appropriate frame for a given application in the laboratory, and for many applications, the relevant frame we need to use is the negative or loss frame.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Andreoni (1999) [1] found that in a linear public goods game, subjects were much more cooperative under a positive frame than a negative frame. Park (2000) [2] and Sonnemans et al (1998) [3] found similar results, which were later decomposed into different components in Cox (2015) [4]. Thus, we must use the appropriate frame for a given application in the laboratory, and for many applications, the relevant frame we need to use is the negative or loss frame.…”
Section: Introductionmentioning
confidence: 62%
“…For these rounds, the higher endowment level results in a greater proportion of individuals choosing Option A than the lower endowment level. As discussed above, this difference does not appear to persist 4 . Now turning to a statistical analysis of the data, the second row of Table 4 contains the results of a logistic regression with random effects, treating the data set as a panel with subjects as the cross-sectional dimension and round as the time dimension.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Prior studies demonstrated that choices could be influenced by the framing (i.e., wording) of decision alternatives [20]. Framing research has shown that different The online framing effect: the moderating role of warning… ways of promoting a specific behavior can influence behavioral intention [31].…”
Section: Framing Effect and Purchase Intentionmentioning
confidence: 99%
“…See also [24][25][26][27] apply an equivalent experimental condition in a one-shot VCM. Both find sizeable demand effects, with the contribution in the Give condition being significantly higher than the contribution in the Take condition.…”
Section: Designmentioning
confidence: 99%